Girl gone viral : a novel - Rai, Alisha (Rai, Alisha. Modern love ;, 2020)
One minute, Katrina King's enjoying an innocent conversation with a hot guy at a coffee shop; the next, a stranger has live-tweeted the entire episode with a romantic meet-cute spin and #CafeBae is the new hashtag-du-jour. The problem? Katrina craves a low-profile life, and going viral threatens the peaceful world she's painstakingly built. Besides, #CafeBae isn't the man she's hungry for . . .With the internet on the hunt for #CuteCafeGirl, Jas Singh - bodyguard, friend and possessor of the most beautiful eyebrows Katrina's ever seen - comes to the rescue and whisks her away to his family's home. Alone in a remote setting with the object of her affections? It's a recipe for romance. But after a long dating dry spell, Katrina isn't sure she can trust her instincts when it comes to love - even if Jas's every look says he wants to be more than just her bodyguard . . ."--Publisher's description.